Methodology for measurements of electrical conductivity of doped silicon carbide - Frisk, Nils-Bertil; Nilsson, Douglas Jutsell (My University, 2014)
This work aims to develop a method for measurements of electric conductivity of doped silicon carbide in powder form. A general purpose measurement cell is used to produce an array of initial results and the experience and conclusions drawn from those are used to refine both the hardware and methodology. The main part of the refinements are focused on how force is applied to the powder and temperature control. The developed method is used to compare and evaluate produced batches of the material. The work concludes with a series of measurements that quantifies the repeatability of the final system together with ideas and suggestions for how the result could be improved.
Keywords: Energi; Elektroteknik; Elektrofysik; Energy; Electrical engineering; Electrophysics